Binding-Induced Diversity of a Human Telomeric G-Quadruplex Stability Phase Space - Domen Oblak; San Hadži; Črtomir Podlipnik; Jurij Lah (MDPI AG, 2022)
The structural polymorphism of G-quadruplex nucleic acids is an important factor in their recognition by proteins and small-molecule ligands. However, it is not clear why the binding of several ligands alters G-quadruplex topology. We addressed this question by following the (un)folding and binding of the human telomeric fragment 5'-(GGGTTA)3GGGT-3' (22GT) by calorimetry (DSC, ITC) and spectroscopy (CD). A thermodynamic analysis of the obtained data led to a detailed description of the topological phase space of stability (phase diagram) of 22GT and shows how it changes in the presence of a specific bisquinolinium ligand (360A). Various 1:1 and 2:1 ligand-quadruplex complexes were observed. With increasing temperature, the 1:1 complexes transformed into 2:1 complexes, which is attributed to the preferential binding of the ligand to the folding intermediates. Overall, the dissection of the thermodynamic parameters in combination with molecular modelling clarified the driving forces of the topological quadruplex transformations in a wide range of ligand concentrations and temperatures.